Desain Website Pelaporan Darurat untuk Mendukung Penanganan Bencana dan Akurasi Pendataan pada Watchroom - Purwanto, Sidiq; Kalbuana, Nawang; Machmiyana, Ichiyu (Innovative: Journal Of Social Science Research, 2025)
This research aims to develop an emergency reporting website to enhance disaster response effectiveness and data accuracy in the watchroom at Yogyakarta International Airport. The system utilizes QR codes to enable first reporters to submit incident reports in real time, which are immediately received by watchroom officers and the ARFF unit. Key features include a reporting form, automatic notifications, location mapping, and an integrated monitoring dashboard. The research applies the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to ensure the system is responsive, secure, and user-friendly. Trial results show the system accelerates reporting, improves coordination, and strengthens communication between visitors and officers. This digital innovation is expected